(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Construction projects have become a changing dramatically in recent decades and that the goal of the beneficiaries of the implementation of structural project is to complete the work with less time and within the cost of the specific and the best possible quality may sometimes happen that highlights the importance of time on the rest of the items at the implementation of projects for various reasons, including the need to use the project as soon as possible possible change rapidly to customer’s requests, but the high cost of the project represents the biggest obstacle for entrepreneurs with its effects on the quality and the time workers, and is a measure of those elements in monetary terms is the key to integration between them, so the cost of the important basics administration in any project and perhaps one ways to rationalize costs is to reduce the time and improve quality in the implementation of construction projects thus less financial implications. And it gained the importance of research of the possibility of the development and application of mechanisms to rationalize costs by using modern methods in projects of fast-track project management, which is technique for stages of construction of the project in terms of the possibility of initiating implementation before the actual completion of the design phase through the project life cycle and the provisions of cost control elements using modern techniques to manage costs.